Python programming essentials - Dennison, Justin; Lowrie, Daniel (Packt Publishing, 2024)
Dive into the fundamentals of Python programming with this comprehensive course designed for beginners and aspiring developers. Starting with an overview of Python's versatility and ease of use, you'll learn how to set up Python on your system, establishing a solid foundation for your programming journey. Initial modules guide you through using Python for simple tasks and decision-making processes, essential for many applications. You'll explore the power of functions, learning to write reusable code to simplify complex problems, and delve into iterations, covering loops and their role in automating repetitive tasks. As you progress, you'll master Python's handling of strings and various data structures, including lists, dictionaries, and tuples. Practical exercises will reinforce your learning, ensuring you can apply these concepts in real-world scenarios. In the latter part of the course, you'll learn to manipulate files using Python, a crucial skill for any developer. The course also covers essential standard library functions, providing tools to extend Python's functionality effortlessly. The final module ties everything together with a capstone project that integrates all the learned concepts. By the end, you'll be proficient in Python programming, ready to tackle diverse coding challenges.
Online resource; title from title details screen (O'Reilly, viewed June 24, 2024)
Keywords: Python (Computer program language); Python (Langage de programmation); Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet